What is the answer of that problem
Problem: 3(x-2)+2
Remember "Please Ask My Dear Aunt Sally"
Step 1: distribute 3 inside the parenthesis
3x-6+2
Step 2: Add like terms
3x - 4
What is the answer of that problem
Problem: 3(x-2)+2
Remember "Please Ask My Dear Aunt Sally"
Step 1: distribute 3 inside the parenthesis
3x-6+2
Step 2: Add like terms
3x - 4
I'm assuming you are looking to solve for the unknown variable, x, when the equation is equal to 0.
If that is the case, the problem is as follows: 3(x - 2) + 2 = 0
You'll first need to distribute the 3 into the terms inside the set of parentheses pertaining to it. That is, multiply 3 by each term inside the parentheses:
3(x - 2) + 2 = 0
(3·x - 3·2) + 2 = 0
(3x - 6) + 2 = 0
3x - 6 + 2 = 0
combine like terms
3x - 4 = 0
add 4 to both sides of the equation
3x - 4 + 4 = 0 + 4
3x = 4
divide both sides of the equation by 3
3x/3 = 4/3
x = 4/3